Measurement of the radial distribution of Cherenkov light generated by TeV γ-ray air showers - Aharonian, Felix A.; Akhperjanian, A. G.; Barrio, J. A.; Bernlöhr, Konrad; Bojahr, H.; Contreras, J. L.; Cortina, J.; Daum, A.; Deckers, T.; Fonseca, V.; Fraß, A.; Gonzalez, J. C.; et al. (Astroparticle physics, 1999)
Using air showers induced by TeV γ-rays from Mrk 501, the radial distribution of Cherenkov light is investigated. The shower geometry is reconstructed from the stereoscopic shower images obtained with the telescopes of the HEGRA IACT system. With the core position known to better than 10 m, the light yield as a function of the distance to the shower axis is derived by comparing event-by-event the image intensities measured in the different telescopes. We observe a change in the shape of the light pool with zenith angle, and a slow variation with shower energy. Data are well reproduced by Monte Carlo air shower simulations.
Gesehen am 23.11.2020